Pengembangan Kreativitas Anak Usia Dini Melalui Kegiatan Seni Lukis di Taman Kanak-Kanak Khadijah Muara Bungo - Pohan, Iffah; Syaputra, Dedi; Muafiroh, Nikmatul; Veronika, Forlen; Siti Hasanah, Wida; Lestari, Ana; Janihon, Janihon (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Painting is an effective method for developing creativity and training fine motor skills in early childhood. This study aims to enhance the creativity of children at Khadijah Muara Bungo Kindergarten through painting activities using colored pencils and other similar tools. The research method involved observation and direct learning in the classroom, allowing the children's development to be observed in real time during the activities. The results of the study show that through painting activities, children are able to express their ideas and feelings more freely, train hand-eye coordination, and increase self-confidence. In addition, painting activities provide a fun learning atmosphere that is not boring and encourages a spirit of exploration. This activity also contributes positively to supporting children's cognitive, social, and emotional development, making it highly relevant for application in the learning process in early childhood education